The policy determinants of hours worked across OECD countries - Causa, Orsetta (OECD Publishing, 2009)
This article investigates the policy determinants of hours worked among employed individuals in OECD countries, focussing on the impact of taxation, working-time regulations, and other labour and product market policies. It explores the factors underlying cross-country differences in hours worked - in line with previous aggregate approaches - while at the same time it looks more closely at labour force heterogeneity - in the vein of microeconomic labour supply models. The paper shows that policies and institutions have a different impact on working hours of men and women. Firstly, while high marginal taxes create a disincentive to work longer hours for women, their impact on hours worked by men is almost insignificant. Secondly, working-time regulations have a significant impact on hours worked by men, and this impact differs across education categories. Thirdly, other labour and product market policies, in particular stringent employment protection of workers on regular contracts and competition-restraining product market policies, have a negative impact on hours worked by men, over and beyond their impact on employment levels